Edukasi Kader Ceting Depiting (Cegah Stunting dengan Pijat Bayi Stunting) Pendamping Keluarga Stunting di Wilayah Kerja Puskesmas Muara Satu Kota Lhokseumawe - Erlina, Erlina; Fitriyani, Aida; Fatiyani, Fatiyani (Jurnal Abdimas Kesehatan (JAK), 2025)
Aceh is a province with the fifth-highest prevalence of stunting in children under five in Indonesia. Based on the results of the Nutrition Case Survey conducted by the Ministry of Health of the Republic of Indonesia in 2021, the stunting rate in Lhokseumawe City was recorded at 27.4 percent, ranking 7th in the Aceh Province. Massage therapy is one of the efforts that can be used to prevent stunting, as it stimulates the growth and development of infants. However, the lack of public knowledge about preventing stunting through massage results in it being performed only under certain conditions by traditional massage practitioners, as there are no skilled personnel or cadres in the villages to perform the massages. Therefore, it is necessary to educate cadres about infant massage as a means of preventing stunting.  The aim of the activity is to educate cadres about CETING DEPITING (Prevent Stunting with Infant Massage) as family companions for stunting prevention in the Muara Satu Community Health Center, Lhokseumawe City. The method of this community service involved educating 11 village cadres, one from each village, about infant massage. The theoretical and practical training was conducted at the health center hall on May 21, 2024, followed by cadre assistance in performing infant massages and evaluations at the integrated health service posts (posyandu) from June 6 to June 8, 2024.  The pre-test results showed that the majority of cadres’ knowledge about infant massage was in the "poor" category (64%). After the education program, their knowledge improved significantly, with 91% categorized as "good." Educating cadres on **Preventing Stunting with Infant Massage (CETING DEPITING) is highly important so that cadres can assist and motivate mothers to perform infant massages as a way to prevent stunting.